Relevance of force-velocity and change of direction assessments for the ranking position in elite junior tennis players - Volk, Nicola Reiner; Vuong, Jo-Lâm; Ferrauti, Alexander (Frontiers in Sports and Active Living, 2023)
This study aimed to correlate sprint mechanical parameters (SMP) of a linear sprint (LS) and a tennis specific modified 505 (Tm505) change of direction (CoD) test obtained with a motorized resistance device (MRD) to the current ranking position (RP). 107 male and 86 female elite junior tennis players nationally ranked in the German Tennis Federation between 10 and 18 years participated in the study. According to their age at peak height velocity (PHV), players were divided into pre-PHV, circa-PHV, and post-PHV groups. Based on laws of motion, SMP were derived from instantaneous time-velocity data of two 20m all-out LS measured with 333Hz. Further, mean values from two Tm505 trials with constant 3kg loading over acceleration-deceleration (1a) and re-acceleration (1b) phases were measured with an MRD. SMP of LS and CoD measurements were partially correlated with the current RP in the overall national ranking by controlling for biological maturation. Low to moderate correlations (ρ=-0.1 – -0.3) were found between SMP and the RP in all male and female age groups. Correlations of the CoD measurements were overall more pronounced, particularly in girls (ρ=-0.44). All linear SMP, like maximal theoretical force (F0; N/kg), and maximal theoretical velocity (v0; m/s), maximal power (Pmax; W/kg), improved over maturation for both genders with Pmax being most important for sprint performance. Further, Pmax was shown to correlate with the girls ranking position (ρ=-0.31). During the Tm505, matured players achieved significantly faster overall total and CoD times. Positioning of CoM before CoD enlarged over maturation and was found to correlate to the RP in both sexes. In addition, nearly all SMP significantly correlated to the primary performance outcomes in the Tm505 test in both genders (r=-0.3 – -0.6). CoD performance has a moderate and higher impact on tennis performance compared to LS. CoD performance as well as Pmax achieved a higher relevance for the ranking position predominantly in girls compared to boys. Hence, particularly Pmax as well as the transfer to on-court CoD motor skills should be a central training goal in elite junior tennis players besides technical skills and should depend on maturation status and gender.